1978
DOI: 10.1002/1520-6807(197801)15:1<4::aid-pits2310150102>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Stability of WISC-R subtest profiles for learning disabled children

Abstract: Stability of the WISC-R subtest profile for 161 learning disabled (LD) children over a 7-month test-retest interval was examined. A unique subtest profile reported earlier (Smith, Coleman, Dokecki, & Davis 1977a) was replicated.Performance IQ was significantly greater than Verbal at both testing occafor Verbal I&.sions. A mean test-retest increase was observed for Per 9 ormance IQ, but not Several investigators have examined WISC subtest scaled scores for learning disabled (LD) children in search of a unique p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…There was essentially no change in the VIQ, but an increase of 3.2 points in the PIQ. These results are consistent with those reported by Vance et al (1981) and Smith (1978). The stability coefficients for the VIQ, PIQ, and FSIQ were .56, .58, and .48, respectively-these values are lower than those reported previously (Smith, 1978;Vance et al, 1981).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There was essentially no change in the VIQ, but an increase of 3.2 points in the PIQ. These results are consistent with those reported by Vance et al (1981) and Smith (1978). The stability coefficients for the VIQ, PIQ, and FSIQ were .56, .58, and .48, respectively-these values are lower than those reported previously (Smith, 1978;Vance et al, 1981).…”
Section: Resultssupporting
confidence: 92%
“…Smith (1978), however, reports that over a 7-month period (October to May), the VIQ was unchanged and the PIQ increased an average of only 4.1 points in a sample of students enrolled in LD programs. Stability of the VIQ and Correspondence should be addressed to Michael Furlong at the University of California, Graduate School of Education, Santa Barbara, CA 93106.…”
mentioning
confidence: 98%
“…The former assumption is based largely on evidence from normal child populations and on a few studies of exceptional children. Smith (1978) studied the stability of WISC-R subtests in 161 children in learning-disabilities classes by retesting them after a 7-month interval. He reported that the test and retest profiles were almost identical with the exception of the Vocabulary subtest, which had dropped significantly.…”
mentioning
confidence: 99%
“…However, their data were only reported in terms of change scores over time, describing the persistent deficits and improvement of functions. Smith (1978) reported the stability of WISC-R subtest profiles for children in learning-disabled classrooms over a 7-month testretest interval. His purpose was to replicate the findings of a unique subtest profile previously reported by -Smith, Coleman, Dokecki, and Davis (1977).…”
mentioning
confidence: 99%